D=rt

c=speed of current

r=speed in still water

t=time

d=72

72=3(r+c)

72=4(r-c)

expand

divide top equation by 3 and bottom by 4

24=r+c

18=r-c

add them equations

42=2r+0c

42=2r

divide both sides by 2

21=r

sub back

18=r-c

18=21-c

minus 21 both sides

-3=-c

3=c

speed of current is 3

speed of ship is 21

**Answer:**

Proven . We get a true statement of 1 = 1 by transforming the expression on the left side to make it look like the right side. See below.

**Step-by-step explanation:**

This is missing some notation: Sin^4x+2cos^2x-cos^4=1

We want to prove : (Sin x ) ^ 4 + 2 (cos x)^2 - (cos x)^4 = 1

Replace the (cos x)^4 with ((cos x)^2)^2 same with the (sin x)^4 with

((sin x)^2)^2

(Sin x ) ^ 4 + 2 (cos x)^2 - (cos x)^4 = 1

( ((sin x)^2) ^2 - ( (cos x)^2)^2 + 2 (cos x)^2 + 1 - 1 = 1

Factor the trinomial -((cos x)^2)^2 + 2 (cos x)^2 + 1 .

considering ((cos x)^2) is the variable

( ((sin x)^2) ^2 - ( (cos x)^2)^2 + 2 (cos x)^2 - 1 + 1 = 1

( ((sin x)^2) ^2 + [- ( (cos x)^2)^2 + 2 (cos x)^2 - 1 ] + 1 = 1

( ((sin x)^2) ^2 - [ ( (cos x)^2) - 1 ]^2 + 1 = 1

But also notice that (sin x)^2 = 1 - (cos x)^2 from the trig identity:

(sin x)^2 + (cos x)^2 = 1

( (1 - (cos x)^2) ^2 - [ ( (cos x)^2) - 1 ]^2 + 1 = 1

here we see that (1 - (cos x)^2) ^2 = [ ( (cos x)^2) - 1 ]^2

so we get ( 0 + 1) = 1

1 = 1 true.

Proven . We are done proving this identity because we get a true statement.

**Answer:**

35x + 65 kg

**Step-by-step explanation:**

Combine like terms. 22x+13x=35x. Final equation: 35x + 65 kg

Ok so how you do it is on the left nearest to the example number line the compound equality would be x then “<“ this sign with the line under it, then “-3”. For the right side you would put “x > 2” respond if you have any questions